Borders and Border Regions in Europe Changes, Challenges and Chances - Lechevalier, Arnaud; Wielgohs (verst.), Jan (Edition Politik, 2013)
Focussing European borders: The book provides insight into a variety of changes in the nature of borders in Europe and its neighborhood from various disciplinary perspectives. Special attention is paid to the history and contemporary dynamics at Polish and German borders. Of particular interest are the creation of Euroregions, mutual perceptions of Poles and Germans at the border, EU Regional Policy, media debates on the extension of the Schengen area. Analysis of cross-border mobility between Abkhazia and Georgia or the impact of Israel's "Security Fence" to Palestine on society complement the focus on Europe with a wider view.